The extraction of orthographic and phonological structure of printed words in adults with dyslexia. (27th September 2021) - Collette, Emilie; Content, Alain; Schelstraete, Marie‐Anne; Chetail, Fabienne
Abstract : The current study investigated the extraction of orthographic and phonological structure of written words in adults with dyslexia. In adults without learning difficulties, Chetail and Content showed that orthographic structure, as determined by the number of vowel letter clusters, influences visual word length estimation. The authors also found a phonological effect determined by the number of syllables of words. In the present study, 22 French‐speaking students diagnosed with dyslexia in childhood and 22 students without learning disabilities were compared. All participants performed the task of estimating word length. The pattern of results obtained by Chetail and Content was replicated: length estimates were biased by both the number of syllables and the number of vowel letter clusters. The study showed a significant interaction between phonological bias and group. The phonological effect was less important in students with dyslexia, suggesting reduced sensitivity to phonological parsing in reading. In contrast, the orthographic effect did not differ significantly between groups, suggesting that the sensitivity to the orthographic structure of written words is preserved in students with dyslexia despite their low‐quality orthographic representations. We conclude that there is no systematic association between sensitivity to the structure of representations and quality of their content.